Identification of novel small-molecule inhibitors targeting menin–MLL interaction, repurposing the antidiarrheal loperamide. Issue 36 (19th August 2016) - Yue, Liyan; Du, Juanjuan; Ye, Fei; Chen, Zhifeng; Li, Lianchun; Lian, Fulin; Zhang, Bidong; Zhang, Yuanyuan; Jiang, Hualiang; Chen, Kaixian; Li, Yuanchao; Zhou, Bing; et al.
Abstract : Scaffold hopping combines with biochemical studies and medicinal chemistry optimizations, leading to potent inhibitors of the menin–MLL interaction. Abstract : Leukemia with a mixed lineage leukemia (MLL) rearrangement, which harbors a variety of MLL fusion proteins, has a poor prognosis despite the latest improved treatment options. Menin has been reported to be a required cofactor for the leukemogenic activity of MLL fusion proteins. Thus, the disruption of the protein–protein interactions between menin and MLL represents a very promising strategy for curing MLL leukemia. Making use of menin–MLL inhibitors with a shape-based scaffold hopping approach, we have discovered that the antidiarrheal loperamide displays previously unreported mild inhibition for the menin–MLL interaction (IC50 = 69 ± 3 μM). In an effort to repurpose this drug, a series of chemical modification analyses was performed, and three of the loperamide-based analogues, DC_YM21, DC_YM25 andDC_YM26 displayed better activities with IC50 values of 0.83 ± 0.13 μM, 0.69 ± 0.07 μM and 0.66 ± 0.05 μM, respectively. Further treatment withDC_YM21 demonstrated potent and selective blockage of proliferation and induction of both cell cycle arrest and differentiation of leukemia cells harboring MLL translocations, which confirmed the specific mechanism of action. In conclusion, molecules of a novel scaffold targeting menin–MLL interactions were reported and they may serve as new potential therapeutic agents for MLL leukemia.